Increasing concentration and competition in European banking: The end of anti-trust? - Philip Malyneux (EIB Papers, 1999)
A trend common to virtually all European banking markets over the last decade or so has been the fall in bank numbers. The decline in number of banks and the associated increase in market concentration may suggest that banking service choice is declining. However, a growth in branch numbers in many systems, increasing foreign bank presence, as well as the growth of non-traditional banking service providers make it difficult to categorically state that overall customer choice is declining. In this section we discuss in more detail how market structure affects performance in the banking sector. This is followed with a discussion of the changing European market structure, and whether increased concentration does actually pose any risks for consumers. The paper concludes with some observations on the impact of mergers on bank performance. Economic theory tells us that there is a relationship between market structure and firm performance. A market characterised by a large number of firms will be expected to operate in a different fashion to a market with one dominant firm. There is a variety of different types of market structure ranging from perfect competition when there are very many firms (and when consumer welfare is maximised), through imperfect competition under an oligopoly, to monopoly.
Keywords: 330; Bank; Wettbewerb; Wirtschaftskonzentration; X-Effizienz; Betriebsgröße; Konzentrationspolitik; EU-Staaten